Impression cytology of the conjunctival epithelium in patients with chronic renal failure - Dursun, D. (2000)
AIMS—To assess ocular surface changes in patients with chronic renal failure (CRF), to compare the results with the degree of corneo-conjunctival calcium deposits, and to determine whether precipitation of calcium salts predisposes ocular surface modifications. METHODS—Impression cytology from 50 CRF patients on regular haemodialysis and 22 age and sex matched control subjects were studied. Specimens were obtained from the temporal bulbar conjunctiva using cellulose acetate filter paper. The samples were fixed in 95% ethanol, stained with the periodic acid Schiff (PAS) stain, and evaluated by light microscopy and were graded by a masked observer. Corneo-conjunctival calcification was graded by the Porter and Crombie classification. RESULTS—In the study group, three patients (6%) disclosed grade 0, 14 patients (28%) grade 1, and 33 patients (66%) grade 2-3 cytological changes. There was a statistically significant difference between the patient and the control groups (p= 0.0007), but no correlation could be found between the impression cytology grades and the calcium deposit grades (p=0.62). CONCLUSION—The ocular surfaces of CRF patients differ significantly from those of normal individuals, and it can be detected using impression cytology. These data suggest that the severity of conjunctival changes are not related to the presence or extent of calcium deposition.